Food waste in the shadow of ideals - a case for practice-oriented design. (7th May 2019) - Hebrok, Marie
Half of the food wasted in the developed world comes from households. However, the sociocultural aspects explaining food waste remain underexplored. By improving our understanding of these causes, more promising interventions may be identified. This article is based on a study of food waste-related practices, and argues that practices rooted in the shared ideals of thrift, health, care and diversity are drivers of food waste in Norwegian households. The article discusses how practice-oriented design can be used to help people live up to their ideals without wasting food in the process. The study is based on 26 interviews with Norwegian households. Other methods included in the study were shop-along, fridge studies and audio and photo documentation. The influence of idealistic practices on levels of food waste should be further explored and exploited by stakeholders in policy, business and design, with the aim of arriving at more contextual solutions and measures.